Technology Transfer Agreement of Multinational Companies in The Framework of Investment Development - Desak Gde Dwi Arini; Diah Gayatri Sudibya; Ni Made Sukaryati Karma (Sociological Jurisprudence Journal, 2021)
The regulation of technology transfer to Multinational Companies (PMN) to date still pays attention to the provisions of the Law of the Republic of Indonesia No. 25 of 2007 on Investment, especially Article 2 paragraph 1, in addition to Indonesia has also adjusted the provisions of national laws in the field of economy/trade with the provisions of GATT and WTO that hav been ratified through the Law of the Republic of Indonesia Number 7 of 1994, including adjustments to the provisions of the field of intellectual property rights (IPR) contained in the TRIPs, such as the Law of the Republic of Indonesia No. 14 of 2001 on Patents, The Law of the Republic of Indonesia No. 15 of 2001 on Brands, and the Law of the Republic of Indonesia No. 19 of 2002 on Copyright, and others covered as objects of intellectual property rights (IPR). The role of multinational companies (PMN) in the transfer of technology can be mentioned, among others: As a holding company that can be used for media, containers, information exchange, technology between countries in the international community which is further used, and useful for Indonesia; As a place for investment in order to obtain benefits for Indonesia; and As a place for the application of new technologies to be useful more efficiently and effectively benefit Indonesia, in addition to improving international economic trade.